Endoscopic Endonasal Resection of Orbital Apex Cavernous Hemangioma: 2-Dimensional Operative Video. Issue 5 (31st May 2019) - Marcellino, Chris R; Peris-Celda, Maria; Link, Michael J; Stokken, Janalee K
Abstract: A 52-yr-old woman was referred to a tertiary medical center for evaluation of 2 yr of progressive visual symptoms and 1 yr of retro-orbital pressure. Her ophthalmologic exam was unrevealing except for mild asymmetrical impairment in color perception. A gadolinium contrast-enhanced magnetic resonance image of the head showed a left extraconal orbital apex lesion consistent with cavernous hemangioma. Computed tomography reveled bony remodeling of the medial-inferior orbital walls with superior orbital fissure expansion. The lesion was endoscopically resected and confirmed by pathological analysis. The endoscopic approach is demonstrated in detail, including correlation with cadaveric anatomic specimens ‡ . During the approach, a rescue nasoseptal flap was raised in case the orbit required further support after tumor resection, but was replaced as this was not needed. This patient had a brief period of postoperative diplopia, which resolved 1 wk after surgery. Her subjective visual deficits and pressure have also resolved. Advantages of the endoscopic approach include improved direct visualization of the lesion, lack of external skin incisions, avoidance of significant neurovascular retraction, and shorter hospital stays than alternative orbitotomy or craniotomy approaches. This 4-handed approach demands endoscopic expertise of 2 surgeons, and is often performed by rhinology-neurosurgery or rhinology-ophthalmology surgical teams. The risk of postoperative diplopia should be discussed with the patient during informed consent. ‡ Anatomic specimen photography courtesy Dr Peris-Celda.